Preparation process of magnetic powder core with high magnetic conductivity and low loss

Through the insulating coating of TiO2@Al2O3 nanowires and insulating composite filler, combined with the double-layer coating of phytic acid and ammonium molybdate, and the introduction of phosphorus, boron and niobium, the problem of magnetic powder core loss in high-frequency environments is solved, and the problem of magnetic powder core loss is achieved. High permeability and low loss magnetic powder core preparation, suitable for large-scale production.

CN119296942AInactive Publication Date: 2025-01-10江西京磁新能源有限责任公司
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411596951.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-permeability magnetic powder cores have significant eddy current losses and hysteresis losses in high-frequency working environments, and are difficult to widely use in large-scale production.

Method used

The insulating coating is used for TiO2@Al2O3 nanowires and insulating composite filler, combined with a double-layer insulating coating structure of phytic acid and ammonium molybdate, and phosphorus, boron and rare earth elements niobium are introduced to optimize the preparation process of the magnetic powder core.

Benefits of technology

Significantly reduce the loss of the magnetic powder core, improve magnetic permeability and magnetoelectric properties, enhance insulation effect, extend service life, and maintain high magnetic permeability in large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119296942A_ABST
    Figure CN119296942A_ABST
Patent Text Reader

Abstract

The invention provides a preparation process of a magnetic powder core with high magnetic conductivity and low loss, and belongs to the technical field of magnetic powder core preparation. The preparation process comprises the following steps: synthesizing the TiO2 coated Al2O3 nanowire; preparing an insulating coating; performing insulation coating on the powder; and preparing the magnetic powder core. Alloy powder is subjected to phytic acid coating firstly and then subjected to ammonium molybdate annealing to be converted into MoO3 coating, phytic acid surface treatment is carried out firstly, phytic acid molecules can react with active sites on the surface of the alloy powder to form an initial insulating layer, and when MoO3 insulating coating is carried out subsequently, the surface of the alloy powder is coated with the MoO3, so that the surface of the alloy powder is coated with the MoO3. MoO3 can be further coated on the basis of an existing phytic acid insulating layer, a double-layer protection structure is constructed, the eddy current loss of the magnetic powder core in an alternating magnetic field can be reduced through phytic acid and MoO3 double-layer insulating coating, and the magnetoelectric performance of the magnetic powder core is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnetic powder core preparation, and in particular to a preparation process of a high-permeability and low-loss magnetic powder core. Background Art

[0002] With the rapid development of electronic technology, electronic equipment is constantly moving towards miniaturization, high frequency and high efficiency, and the performance requirements for magnetic materials are also increasing. As an important magnetic material, magnetic powder cores have been widely used in many fields such as power electronics, communications, aerospace, etc. High permeability and low loss magnetic powder cores have excellent magnetic properties and can meet the needs of modern electronic equipment for high efficiency and high stability of magnetic components, becoming one of the hot spots in current magnetic material research.

[0003] The common high magnetic permeability powder cores on the market are mainly based on iron-based alloy materials, such as Fe-Si, Fe-Ni, etc., and are prepared by powder metallurgy. Although these materials meet the basic electromagnetic performance requirements to a certain extent, there are still significant eddy current loss and hysteresis loss problems in high-frequency working environments. Eddy current loss originates from the induced current between particles inside the magnetic core under the alternating magnetic field, while hysteresis loss is related to the reorientation of magnetic domains during the magnetization process. Both together lead to a decrease in energy efficiency.

[0004] To further reduce losses, studies have explored material miniaturization, component modification, and the use of special molding and heat treatment processes, but these methods either sacrifice a certain amount of magnetic permeability or significantly increase the preparation cost, making them difficult to be widely used in large-scale production.

[0005] Therefore, we proposed a preparation process for high permeability and low loss magnetic powder cores that can maintain high permeability while significantly reducing losses. Summary of the invention

[0006] In view of the shortcomings of the prior art, the object of the present invention is to provide a preparation process for a high magnetic permeability and low loss magnetic powder core.

[0007] A preparation process of a high magnetic permeability and low loss magnetic powder core comprises the following steps:

[0008] S1: Synthesis of TiO2@Al2O3 Nanowires

[0009] The titanium dioxide nanoparticles are added into a sodium hydroxide solution for reaction treatment to obtain TiO2 nanowires, and the TiO2 nanowires are mixed with polyvinyl pyrrolidone, deionized water, aluminum chloride hexahydrate and aluminum sulfate 18hydrate to obtain TiO2@Al2O3 nanowires;

[0010] S2: Preparation of insulating coating

[0011] An insulating composite filler is prepared by modifying TiO2@Al2O3 nanowires with ethylenediamine, and an insulating coating is prepared by using the insulating composite filler, epoxy resin and acetone as raw materials.

[0012] S3: Insulation coating of powder

[0013] 50-60 parts by weight of FeSiAl, 1-2 parts by weight of Cu, 5-6 parts by weight of ferroboron, 2-3 parts by weight of ferroniobium and 3-5 parts by weight of ferrophosphorus powder are prepared by gas atomization, the prepared FeSiAl powder is mixed with Cu, ferroboron, ferroniobium and ferrophosphorus powder, and then calcined to obtain alloy powder, the alloy powder is coated with phytic acid and then annealed with ammonium molybdate to be converted into MoO3 coating to obtain an insulation coated powder;

[0014] S4: Preparation of magnetic powder core

[0015] Lubricants and binders are added to the powder after insulation coating to obtain magnetic powder to be formed, which is then pressed and calcined to obtain a semi-finished magnetic powder core, and an insulating coating is sprayed on the semi-finished magnetic powder core to obtain a magnetic powder core.

[0016] Furthermore, step S1 of synthesizing TiO2@Al2O3 nanowires specifically includes the following steps:

[0017] S1.1: Add 2-3 parts by weight of titanium dioxide nanoparticles to 5-8 parts by weight of 10M sodium hydroxide solution and ultrasonically treat for 30-40 minutes, then transfer to a high-pressure reactor with Teflon, react at 200-230°C for 24-25 hours, wash the reaction product to neutrality after the reaction is completed, and then soak the reaction product in 0.2M hydrogen chloride solution for 4-5 hours, then wash and dry, and anneal at 200-220°C for 3-5 hours to obtain TiO2 nanowires;

[0018] S1.2: adding 0.01-0.03 parts by weight of polyvinyl pyrrolidone to 150-200 parts by weight of deionized water, and then adding 1-2 parts by weight of TiO2 nanowires, ultrasonicating for 20-30 minutes and then mechanically stirring for 1-2 hours to obtain a mixed solution I;

[0019] S1.3: 0.15-0.2 parts by weight of aluminum chloride hexahydrate and 0.3-0.5 parts by weight of aluminum sulfate 18hydrate are placed in a beaker, 1-2 parts by weight of deionized water are added, and the mixture is stirred at 10-20 r / min to obtain a mixed solution II;

[0020] S1.4: In a 55-60°C water bath, add mixed solution II dropwise into mixed solution I using a separatory funnel, then stir and mix for 1-2 hours, collect the solid product, and then centrifuge, wash and dry to obtain TiO2@Al2O3 nanowires.

[0021] Furthermore, step S2 of preparing the insulating coating specifically comprises the following steps:

[0022] S2.1: 2-3 parts by weight of ethylenediamine are added to 50-80 parts by weight of deionized water using a pipette under magnetic stirring in a fume hood to obtain a diluted ethylenediamine solution;

[0023] S2.2: Add 0.5-1 parts by weight of TiO2@Al2O3 nanowires to 100-120 parts by weight of deionized water, perform ultrasonic treatment for 20-30 minutes, heat to 85-90°C, then add the above-mentioned ethylenediamine dilution solution, stir for 1-2 hours, and after the reaction is completed, centrifuge, wash and dry to obtain an insulating composite filler;

[0024] S2.3: Dissolve 2-3 parts by weight of bisphenol-F type epoxy resin DER354 monomer in 5-8 parts by weight of acetone solvent, and ultrasonically disperse for 20-30 minutes to obtain a clear solution. Then, add 0.5-1 parts by weight of insulating composite filler, stir and mix for 4-5 hours, and then add 0.6-0.8 parts by weight of curing agent Epikure-W, stir and mix evenly to obtain an insulating coating.

[0025] Furthermore, step S3 of insulating the powder specifically comprises the following steps:

[0026] S3.1: Prepare 50-60 parts by weight of FeSiAl, 1-2 parts by weight of Cu, 5-6 parts by weight of ferroboron, 2-3 parts by weight of ferroniobium and 3-5 parts by weight of ferrophosphorus powder by gas atomization, then mix the prepared FeSiAl powder with Cu, ferroboron, ferroniobium and ferrophosphorus powders and anneal at a high temperature in the range of 700-850° C. for 1.5-3 h under protective gas to obtain alloy powder;

[0027] S3.2: Add 2-3 parts by weight of the alloy powder to 5-8 parts by weight of a 5wt% phytic acid aqueous solution, stir and mix at 30-35°C for 60-70 minutes, then perform vacuum filtration, and dry the resulting precipitate in a dryer at 60-70°C to obtain a treated alloy powder;

[0028] S3.3: Disperse 2-3 parts by weight of the treated alloy powder in a 20-25% ammonium molybdate-water solution, stir at room temperature for 3-5 hours, and then anneal at 400-420°C for 1-2 hours to obtain an insulation-coated powder.

[0029] Furthermore, step S4 of preparing the magnetic powder core specifically includes the following steps:

[0030] S4.1: Add 0.6-0.8wt% lubricant and 1.5-2wt% binder to the powder after insulation coating, mix evenly with a sieve to obtain magnetic powder to be formed;

[0031] S4.2: Pressing the magnetic powder to be formed into a powder core blank at a pressing pressure of 1800-2000 MPa, and keeping the pressed powder core blank at 700-800° C. for 60-70 min under high vacuum conditions to obtain a semi-finished magnetic powder core;

[0032] S4.3: Spray insulating coating onto the surface of the semi-finished magnetic powder core, then keep it in an oven at 40-50°C for 1-2h, then keep it at 120-130°C for 2-3h, keep it at 177-180°C for 4-5h, and finally keep it at 200-220°C for 6-7h to obtain the magnetic powder core.

[0033] Furthermore, the ferroboron in step S3.1 is specifically ferroboron with a boron content of 20.3 wt%.

[0034] Furthermore, the ferroniobium in step S3.1 is specifically ferroniobium with a niobium content of 61.2 wt%.

[0035] Furthermore, the ferrophosphorus in step S3.1 is specifically ferrophosphorus with a phosphorus content of 18.5 wt%.

[0036] Furthermore, in step S4.1, the lubricant is zinc stearate lubricant.

[0037] Furthermore, in step S4.1, the adhesive is a silicone resin adhesive.

[0038] Compared with the prior art, the present invention has at least the following beneficial effects:

[0039] 1. The present invention first coats the alloy powder with phytic acid and then anneals the alloy powder with ammonium molybdate to form MoO3 coating. The phytic acid surface treatment is first performed, and the phytic acid molecules can react with the active sites on the surface of the alloy powder to form an initial insulating layer. The phytic acid molecules can be well adsorbed and chemically bonded on the powder surface. The phytic acid molecules can fill the tiny irregularities on the powder surface to provide a preliminary insulating barrier. When MoO3 insulating coating is performed later, the oxygen atoms of the phosphate groups in the phytic acid molecules can provide lone pairs of electrons to the empty orbits of the molybdenum atoms in MoO3, thereby forming a The formation of such coordination bonds can make MoO3 directionally adsorbed on the phytic acid insulating layer. Therefore, MoO3 can be further coated on the basis of the existing phytic acid insulating layer to construct a double-layer protective structure. Compared with a single insulating coating, the double-layer coating can more comprehensively cover the surface of the alloy powder, reduce the holes or weak points of the coating, and improve the integrity of the insulating coating. A good insulating coating can effectively insulate a single powder particle. The double-layer insulating coating of phytic acid and MoO3 can reduce the eddy current loss of the magnetic powder core in the alternating magnetic field and improve the magnetoelectric properties of the magnetic powder core.

[0040] 2. The present invention adds insulating composite fillers to the insulating coating. The TiO2@Al2O3 nanowires in the insulating composite fillers can form a network structure in the coating, effectively fill the tiny pores inside the coating, and construct a denser insulating layer. They can fill the microscopic gaps in the insulating coating, reduce the possibility of forming a conductive path, and thus effectively reduce the eddy current loss in the magnetic powder core. The modification of ethylenediamine helps to evenly disperse the insulating composite fillers in the insulating coating. The evenly dispersed insulating composite fillers can more comprehensively cover the surface of the magnetic powder core to form a continuous and uniform insulating layer, further enhance the insulation effect, and effectively reduce the eddy current loss in the magnetic powder core. The insulating composite fillers can affect the movement of the magnetic domain walls of the magnetic powder core, stabilize the magnetic domain walls to a certain extent, and make the magnetic domain walls move more orderly under the action of the magnetic field, thereby improving the magnetic permeability of the magnetic powder core. At the same time, the insulating coating can prevent moisture, oxygen or corrosive gases from contacting the magnetic powder core, maintain the high magnetic permeability and low loss performance of the magnetic powder core, and extend the service life of the magnetic powder core.

[0041] 3. The present invention introduces phosphorus, boron and rare earth element niobium into the magnetic powder core. After phosphorus atoms are introduced into the magnetic powder core, the phosphorus atoms at the grain boundaries can hinder the movement of the magnetic domain wall, thereby refining the magnetic domain structure. The refined magnetic domain structure helps to achieve a larger change in magnetization intensity under a smaller magnetic field change, thereby improving the magnetic permeability of the magnetic powder core; boron atoms can form chemical bonds with the surrounding metal atoms, thereby enhancing the binding force of the grain boundaries, thereby maintaining the stable performance of the magnetic powder core; niobium, as a rare earth element, can inhibit the growth of grains through diffusion and aggregation in the magnetic powder core. During the preparation process of the magnetic powder core, niobium atoms will form pinning points at the grain boundaries, hindering the migration of the grain boundaries, thereby refining the grains. By introducing phosphorus, boron and rare earth element niobium and optimizing their contents, the prepared magnetic powder core has good magnetic performance stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the invention and, together with the description, further serve to explain the principles of the invention and to enable those skilled in the relevant art to make and use the invention.

[0043] Figure 1 The present invention is a flowchart of a process for preparing a high permeability and low loss magnetic powder core used in an embodiment of the present invention. DETAILED DESCRIPTION

[0044] The following is a detailed description of a preparation process of a high permeability and low loss magnetic powder core provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0045] Example 1

[0046] A preparation process of a high permeability and low loss magnetic powder core, such as Figure 1 As shown, the following steps are included:

[0047] S1: Synthesis of TiO2@Al2O3 Nanowires

[0048] S1.1: Add 2 parts by weight of titanium dioxide nanoparticles to 5 parts by weight of 10M sodium hydroxide solution and ultrasonically treat for 30 minutes, then transfer to a high-pressure reactor with Teflon and react at 200°C for 24 hours. After the reaction is completed, wash the reaction product to neutrality, and then soak the reaction product in 0.2M hydrogen chloride solution for 4 hours, then wash and dry, and anneal at 200°C for 3 hours to obtain TiO2 nanowires;

[0049] S1.2: 0.01 parts by weight of polyvinyl pyrrolidone was added to 150 parts by weight of deionized water, and then 1 part by weight of TiO2 nanowires was added, and then ultrasonicated for 20 minutes and then mechanically stirred for 1 hour to obtain a mixed solution I;

[0050] S1.3: 0.15 parts by weight of aluminum chloride hexahydrate and 0.3 parts by weight of aluminum sulfate 18hydrate were placed in a beaker, 1 part by weight of deionized water was added, and the mixture was stirred at 10 r / min to obtain a mixed solution II;

[0051] S1.4: In a 55°C water bath, add the mixed solution II dropwise into the mixed solution I using a separatory funnel, and then stir and mix for 1 h. Collect the solid product, and then centrifuge, wash and dry to obtain TiO2@Al2O3 nanowires.

[0052] S2: Preparation of insulating coating

[0053] S2.1: 2 parts by weight of ethylenediamine are added to 50 parts by weight of deionized water using a pipette under magnetic stirring in a fume hood to obtain a diluted ethylenediamine solution;

[0054] S2.2: 0.5 parts by weight of TiO2@Al2O3 nanowires are added to 100 parts by weight of deionized water, and the mixture is ultrasonically treated for 20 minutes and then heated to 85°C. The diluted ethylenediamine solution is then added and stirred for 1 hour. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain an insulating composite filler.

[0055] S2.3: 2 parts by weight of bisphenol-F epoxy resin DER354 monomer was dissolved in 5 parts by weight of acetone solvent, and ultrasonic dispersion was performed for 20 minutes to obtain a clear solution, and then 0.5 parts by weight of insulating composite filler was added, and stirred and mixed for 4 hours, and then 0.6 parts by weight of curing agent Epikure-W was added, and stirred and mixed evenly to obtain an insulating coating;

[0056] S3: Insulation coating of powder

[0057] S3.1: 50 parts by weight of FeSiAl, 1 part by weight of Cu, 5 parts by weight of ferroboron with a boron content of 20.3wt%, 2 parts by weight of ferroniobium with a niobium content of 61.2wt% and 3 parts by weight of ferrophosphorus powder with a phosphorus content of 18.5wt% are prepared by gas atomization, and then the prepared FeSiAl powder is mixed with Cu, ferroboron, ferroniobium and ferrophosphorus powders and annealed at a high temperature of 700°C for 1.5h under protective gas to obtain alloy powder;

[0058] S3.2: Add 2 parts by weight of the alloy powder to 5 parts by weight of a 5 wt% phytic acid aqueous solution, stir and mix at 30°C for 60 minutes, then perform vacuum filtration, and dry the resulting precipitate in a dryer at 60°C to obtain a treated alloy powder;

[0059] S3.3: Disperse 2 parts by weight of the treated alloy powder in a 20% ammonium molybdate-water solution, stir at room temperature for 3 hours, and then anneal at 400° C. for 1 hour to obtain an insulation-coated powder;

[0060] S4: Preparation of magnetic powder core

[0061] S4.1: Add 0.6wt% zinc stearate lubricant and 1.5wt% silicone resin binder to the powder after insulation coating, mix evenly with a sieve to obtain magnetic powder to be formed;

[0062] S4.2: The magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 1800 MPa, and the pressed powder core blank is kept at 700° C. for 60 min under high vacuum conditions to obtain a semi-finished magnetic powder core;

[0063] S4.3: Spray insulating coating onto the surface of the semi-finished magnetic powder core, then keep it in an oven at 40°C for 1 hour, then keep it at 120°C for 2 hours, keep it at 177°C for 4 hours, and finally keep it at 200°C for 6 hours to obtain the magnetic powder core.

[0064] Example 2

[0065] A preparation process of a high permeability and low loss magnetic powder core, such as Figure 1 As shown, the following steps are included:

[0066] S1: Synthesis of TiO2@Al2O3 Nanowires

[0067] S1.1: 3 parts by weight of titanium dioxide nanoparticles are added to 8 parts by weight of 10M sodium hydroxide solution and ultrasonically treated for 30 minutes, then transferred to a high-pressure reactor with Teflon and reacted at 200°C for 24 hours. After the reaction is completed, the reaction product is washed to neutrality, and then immersed in 0.2M hydrogen chloride solution for 4-5 hours, then washed and dried, and annealed at 200°C for 3 hours to obtain TiO2 nanowires;

[0068] S1.2: 0.03 parts by weight of polyvinyl pyrrolidone was added to 200 parts by weight of deionized water, and then 2 parts by weight of TiO2 nanowires were added, and the mixture was ultrasonicated for 20 minutes and then mechanically stirred for 1 hour to obtain a mixed solution I;

[0069] S1.3: 0.2 parts by weight of aluminum chloride hexahydrate and 0.5 parts by weight of aluminum sulfate 18hydrate were placed in a beaker, 2 parts by weight of deionized water were added, and the mixture was stirred at 10 r / min to obtain a mixed solution II;

[0070] S1.4: In a 55°C water bath, add the mixed solution II dropwise into the mixed solution I using a separatory funnel, and then stir and mix for 1 h. Collect the solid product, and then centrifuge, wash and dry to obtain TiO2@Al2O3 nanowires.

[0071] S2: Preparation of insulating coating

[0072] S2.1: 3 parts by weight of ethylenediamine are added to 80 parts by weight of deionized water using a pipette under magnetic stirring in a fume hood to obtain a diluted ethylenediamine solution;

[0073] S2.2: 1 part by weight of TiO2@Al2O3 nanowires was added to 120 parts by weight of deionized water, and the mixture was ultrasonically treated for 20 minutes and then heated to 85°C. Then, the above-mentioned ethylenediamine dilution solution was added and stirred for 1 hour. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain an insulating composite filler;

[0074] S2.3: 3 parts by weight of bisphenol-F epoxy resin DER354 monomer was dissolved in 8 parts by weight of acetone solvent, and ultrasonic dispersion was performed for 20 minutes to obtain a clear solution, and then 1 part by weight of insulating composite filler was added, and stirred and mixed for 4 hours, and then 0.8 parts by weight of curing agent Epikure-W was added, and stirred and mixed evenly to obtain an insulating coating;

[0075] S3: Insulation coating of powder

[0076] S3.1: 60 parts by weight of FeSiAl, 2 parts by weight of Cu, 6 parts by weight of ferroboron with a boron content of 20.3wt%, 3 parts by weight of ferroniobium with a niobium content of 61.2wt% and 5 parts by weight of ferrophosphorus powder with a phosphorus content of 18.5wt% are prepared by gas atomization, and then the prepared FeSiAl powder is mixed with Cu, ferroboron, ferroniobium and ferrophosphorus powders and annealed at a high temperature of 700°C for 1.5h under protective gas to obtain alloy powder;

[0077] S3.2: Add 3 parts by weight of the alloy powder to 8 parts by weight of a 5 wt% phytic acid aqueous solution, stir and mix at 30°C for 60 minutes, then perform vacuum filtration, and dry the resulting precipitate in a dryer at 60°C to obtain a treated alloy powder;

[0078] S3.3: Disperse 3 parts by weight of the treated alloy powder in a 25% ammonium molybdate-water solution, stir at room temperature for 3 hours, and then anneal at 400° C. for 1 hour to obtain an insulation-coated powder;

[0079] S4: Preparation of magnetic powder core

[0080] S4.1: Add 0.8wt% zinc stearate lubricant and 2wt% silicone resin binder to the powder after insulation coating, mix evenly with a sieve to obtain magnetic powder to be formed;

[0081] S4.2: The magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 1800 MPa, and the pressed powder core blank is kept at 700° C. for 60 min under high vacuum conditions to obtain a semi-finished magnetic powder core;

[0082] S4.3: Spray insulating coating onto the surface of the semi-finished magnetic powder core, then keep it in an oven at 40°C for 1 hour, then keep it at 120°C for 2 hours, keep it at 177°C for 4 hours, and finally keep it at 200°C for 6 hours to obtain the magnetic powder core.

[0083] Example 3

[0084] A preparation process of a high permeability and low loss magnetic powder core, such as Figure 1 As shown, the following steps are included:

[0085] S1: Synthesis of TiO2@Al2O3 Nanowires

[0086] S1.1: Add 2 parts by weight of titanium dioxide nanoparticles to 5 parts by weight of 10M sodium hydroxide solution and ultrasonically treat for 40 minutes, then transfer to a high-pressure reactor with Teflon and react at 230°C for 25 hours. After the reaction is completed, wash the reaction product to neutrality, and then soak the reaction product in 0.2M hydrogen chloride solution for 5 hours, then wash and dry, and anneal at 220°C for 5 hours to obtain TiO2 nanowires;

[0087] S1.2: 0.01 parts by weight of polyvinyl pyrrolidone was added to 150 parts by weight of deionized water, and then 1 part by weight of TiO2 nanowires was added, and then ultrasonicated for 30 minutes and then mechanically stirred for 2 hours to obtain a mixed solution I;

[0088] S1.3: 0.15 parts by weight of aluminum chloride hexahydrate and 0.3 parts by weight of aluminum sulfate 18hydrate are placed in a beaker, 1 part by weight of deionized water is added, and the mixture is stirred at 20 r / min to obtain a mixed solution II;

[0089] S1.4: In a 60°C water bath, add the mixed solution II dropwise into the mixed solution I using a separatory funnel, and then stir and mix for 2 h. Collect the solid product, and then centrifuge, wash and dry to obtain TiO2@Al2O3 nanowires.

[0090] S2: Preparation of insulating coating

[0091] S2.1: 2 parts by weight of ethylenediamine are added to 50 parts by weight of deionized water using a pipette under magnetic stirring in a fume hood to obtain a diluted ethylenediamine solution;

[0092] S2.2: 0.5 parts by weight of TiO2@Al2O3 nanowires are added to 100 parts by weight of deionized water, and the mixture is ultrasonically treated for 30 minutes and then heated to 90°C. The diluted ethylenediamine solution is then added and stirred for 2 hours. After the reaction is completed, the mixture is centrifuged, washed and dried to obtain an insulating composite filler.

[0093] S2.3: 2 parts by weight of bisphenol-F epoxy resin DER354 monomer was dissolved in 5 parts by weight of acetone solvent, and ultrasonic dispersion was performed for 30 minutes to obtain a clear solution, and then 0.5 parts by weight of insulating composite filler was added, and stirred and mixed for 5 hours, and then 0.6 parts by weight of curing agent Epikure-W was added, and stirred and mixed evenly to obtain an insulating coating;

[0094] S3: Insulation coating of powder

[0095] S3.1: Prepare 50 parts by weight of FeSiAl, 1 part by weight of Cu, 5 parts by weight of ferroboron with a boron content of 20.3wt%, 2 parts by weight of ferroniobium with a niobium content of 61.2wt% and 3 parts by weight of ferrophosphorus powder with a phosphorus content of 18.5wt% by gas atomization, then mix the prepared FeSiAl powder with Cu, ferroboron, ferroniobium and ferrophosphorus powders and anneal at a high temperature of 850°C for 3h under protective gas to obtain alloy powder;

[0096] S3.2: Add 2 parts by weight of the alloy powder to 5 parts by weight of a 5 wt% phytic acid aqueous solution, stir and mix at 35°C for 70 minutes, then perform vacuum filtration, and dry the resulting precipitate in a dryer at 70°C to obtain a treated alloy powder;

[0097] S3.3: Disperse 2 parts by weight of the treated alloy powder in a 20% ammonium molybdate-water solution, stir at room temperature for 5 hours, and then anneal at 420° C. for 2 hours to obtain an insulation-coated powder;

[0098] S4: Preparation of magnetic powder core

[0099] S4.1: Add 0.6wt% zinc stearate lubricant and 1.5wt% silicone resin binder to the powder after insulation coating, mix evenly with a sieve to obtain magnetic powder to be formed;

[0100] S4.2: The magnetic powder to be formed is pressed into a powder core blank at a pressing pressure of 2000 MPa, and the pressed powder core blank is kept at 800° C. for 70 min under high vacuum conditions to obtain a semi-finished magnetic powder core;

[0101] S4.3: Spray insulating coating onto the surface of the semi-finished magnetic powder core, then keep it in an oven at 50°C for 2 hours, then keep it at 130°C for 3 hours, keep it at 180°C for 5 hours, and finally keep it at 220°C for 7 hours to obtain the magnetic powder core.

[0102] The magnetic performance tests were carried out on Examples 1-3, and the test results are shown in Table 1.

[0103] Testing process:

[0104] 100kHz effective permeability μ e :Use precision magnetic analyzer to measure the effective magnetic permeability μ at a frequency of 100kHz e , the test voltage is fixed at 1V.

[0105] Loss Pc at 50kHz / 50mT: The volume loss Pc at a frequency of 50kHz and a magnetic flux density of 50mT is measured using an AC loss test system.

[0106] Comparative Example 1

[0107] Compared with Example 1, the difference of Comparative Example 1 is that the insulating composite filler in steps S1, S2.1-S2.2 and S2.3 is removed in Comparative Example 1, and the remaining steps remain unchanged to prepare the magnetic powder core, which is recorded as Comparative Example 1.

[0108] The magnetic properties of Examples 1-3 and Comparative Example 1 were tested, and the test results are shown in Table 1.

[0109] Table 1. Magnetic properties of magnetic powder cores of Examples 1-3 and Comparative Examples 1-3

[0110] <![CDATA[Effective permeability μ at 100 kHz e > <![CDATA[Power loss Pc (mW / cm 3 )]]> Example 1 118 45.8 Example 2 115 46.2 Example 3 116 45.9 Comparative Example 1 83 68.4

[0111] It can be seen from the data in Table 1 that the magnetic powder core prepared by the present invention has higher magnetic permeability and lower loss. After adding insulating composite filler to the insulating coating, the eddy current loss in the magnetic powder core is effectively reduced, thereby reducing the loss and improving the magnetic permeability of the magnetic powder core.

[0112] Comparative Example 2

[0113] Compared with Example 1, the difference of Comparative Example 2 is that step S3.2 is removed in Comparative Example 2, and the treated alloy powder in step S3.3 is replaced with alloy powder of equal mass, and the remaining steps remain unchanged to prepare the magnetic powder core, which is recorded as Comparative Example 2.

[0114] Comparative Example 3

[0115] Compared with Example 1, the difference of Comparative Example 3 is that step S3.3 is removed, the insulation coated powder in step S4.1 is replaced with the treated alloy powder, and the remaining steps remain unchanged to prepare the magnetic powder core, which is recorded as Comparative Example 3.

[0116] Comparative Example 4

[0117] Compared with Example 1, the difference of Comparative Example 4 is that Comparative Example 4 removes steps S2.1-S2.2, replaces the insulating composite filler in step S2.3 with an equal weight portion of TiO2@Al2O3 nanowires, and prepares the magnetic powder core without changing the other steps, which is recorded as Comparative Example 4.

[0118] The loss data of Example 1 is used, and loss tests are performed on Comparative Examples 2-4. The measurement results are shown in Table 2.

[0119] Table 2. Loss test of Example 1 and Comparative Examples 2-3

[0120] Loss Pc(mW / cm3) Example 1 45.8 Comparative Example 2 73.2 Comparative Example 3 75.3 Comparative Example 4 58.4

[0121] It can be seen from the data in Table 2 that the double-layer protective structure constructed by first coating the alloy powder with phytic acid and then annealing it with ammonium molybdate to convert it into MoO3 coating can reduce the loss of the magnetic powder core in the alternating magnetic field and improve the magnetoelectric properties of the magnetic powder core compared to a single insulating coating. It can be seen from the data in Comparative Example 4 that modification with ethylenediamine helps to reduce the loss in the magnetic powder core.

[0122] Comparative Example 5

[0123] Compared with Example 1, the difference of Comparative Example 5 is that ferroboron, ferroniobium and ferrophosphorus in step S3.1 are removed, and the remaining steps are unchanged to prepare the magnetic powder core, which is recorded as Comparative Example 5.

[0124] The effective magnetic permeability data of Example 1 is used, and the magnetic permeability test is performed on Comparative Example 5. The measurement results are shown in Table 3.

[0125] Table 3. Magnetic permeability test of Example 1 and Comparative Example 5

[0126] <![CDATA[Effective permeability μ at 100 kHz e > Example 1 118 Comparative Example 4 72

[0127] It can be seen from the data in Table 3 that the introduction of phosphorus, boron and the rare earth element niobium into the magnetic powder core effectively improves the magnetic permeability of the magnetic powder core.

[0128] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A process for preparing a high permeability and low loss magnetic powder core, characterized in that: The steps include: S1: Synthesis of TiO2@Al2O3 Nanowires The titanium dioxide nanoparticles are added into a sodium hydroxide solution for reaction treatment to obtain TiO2 nanowires, and the TiO2 nanowires are mixed with polyvinyl pyrrolidone, deionized water, aluminum chloride hexahydrate and aluminum sulfate 18hydrate to obtain TiO2@Al2O3 nanowires; S2: Preparation of insulating coating An insulating composite filler is prepared by modifying TiO2@Al2O3 nanowires with ethylenediamine, and an insulating coating is prepared by using the insulating composite filler, epoxy resin and acetone as raw materials. S3: Insulation coating of powder 50-60 parts by weight of FeSiAl, 1-2 parts by weight of Cu, 5-6 parts by weight of ferroboron, 2-3 parts by weight of ferroniobium and 3-5 parts by weight of ferrophosphorus powder are prepared by gas atomization, the prepared FeSiAl powder is mixed with Cu, ferroboron, ferroniobium and ferrophosphorus powder, and then calcined to obtain alloy powder, the alloy powder is coated with phytic acid and then annealed with ammonium molybdate to be converted into MoO3 coating to obtain an insulation coated powder; S4: Preparation of magnetic powder core Lubricants and binders are added to the powder after insulation coating to obtain magnetic powder to be formed, which is then pressed and calcined to obtain a semi-finished magnetic powder core, and an insulating coating is sprayed on the semi-finished magnetic powder core to obtain a magnetic powder core.

2. The process for preparing a high permeability and low loss magnetic powder core according to claim 1, characterized in that: Step S1 Synthesis of TiO2@Al2O3 nanowires, specifically comprising the following steps: S1.1: Add 2-3 parts by weight of titanium dioxide nanoparticles to 5-8 parts by weight of 10M sodium hydroxide solution and ultrasonically treat for 30-40 minutes, then transfer to a high-pressure reactor with Teflon, react at 200-230°C for 24-25 hours, wash the reaction product to neutrality after the reaction is completed, and then soak the reaction product in 0.2M hydrogen chloride solution for 4-5 hours, then wash and dry, and anneal at 200-220°C for 3-5 hours to obtain TiO2 nanowires; S1.2: adding 0.01-0.03 parts by weight of polyvinyl pyrrolidone to 150-200 parts by weight of deionized water, and then adding 1-2 parts by weight of TiO2 nanowires, ultrasonicating for 20-30 minutes and then mechanically stirring for 1-2 hours to obtain a mixed solution I; S1.3: 0.15-0.2 parts by weight of aluminum chloride hexahydrate and 0.3-0.5 parts by weight of aluminum sulfate 18hydrate are placed in a beaker, 1-2 parts by weight of deionized water are added, and the mixture is stirred at 10-20 r / min to obtain a mixed solution II; S1.4: In a 55-60°C water bath, add mixed solution II dropwise into mixed solution I using a separatory funnel, then stir and mix for 1-2 hours, collect the solid product, and then centrifuge, wash and dry to obtain TiO2@Al2O3 nanowires.

3. The process for preparing a high permeability and low loss magnetic powder core according to claim 2, characterized in that: Step S2: Preparation of insulating coating, specifically comprising the following steps: S2.1: 2-3 parts by weight of ethylenediamine are added to 50-80 parts by weight of deionized water using a pipette under magnetic stirring in a fume hood to obtain a diluted ethylenediamine solution; S2.2: Add 0.5-1 parts by weight of TiO2@Al2O3 nanowires to 100-120 parts by weight of deionized water, perform ultrasonic treatment for 20-30 minutes, heat to 85-90°C, then add the above-mentioned ethylenediamine dilution solution, stir for 1-2 hours, and after the reaction is completed, centrifuge, wash and dry to obtain an insulating composite filler; S2.3: Dissolve 2-3 parts by weight of bisphenol-F type epoxy resin DER354 monomer in 5-8 parts by weight of acetone solvent, and ultrasonically disperse for 20-30 minutes to obtain a clear solution. Then, add 0.5-1 parts by weight of insulating composite filler, stir and mix for 4-5 hours, and then add 0.6-0.8 parts by weight of curing agent Epikure-W, stir and mix evenly to obtain an insulating coating.

4. The process for preparing a high permeability and low loss magnetic powder core according to claim 3, characterized in that: Step S3: insulation coating of the powder, specifically comprising the following steps: S3.1: Prepare 50-60 parts by weight of FeSiAl, 1-2 parts by weight of Cu, 5-6 parts by weight of ferroboron, 2-3 parts by weight of ferroniobium and 3-5 parts by weight of ferrophosphorus powder by gas atomization, then mix the prepared FeSiAl powder with Cu, ferroboron, ferroniobium and ferrophosphorus powders and anneal at a high temperature in the range of 700-850° C. for 1.5-3 h under protective gas to obtain alloy powder; S3.2: Add 2-3 parts by weight of the alloy powder to 5-8 parts by weight of a 5wt% phytic acid aqueous solution, stir and mix at 30-35°C for 60-70 minutes, then perform vacuum filtration, and dry the resulting precipitate in a dryer at 60-70°C to obtain a treated alloy powder; S3.3: Disperse 2-3 parts by weight of the treated alloy powder in a 20-25% ammonium molybdate-water solution, stir at room temperature for 3-5 hours, and then anneal at 400-420°C for 1-2 hours to obtain an insulation-coated powder.

5. The process for preparing a high permeability and low loss magnetic powder core according to claim 4, characterized in that: Step S4: Preparation of magnetic powder core, specifically comprising the following steps: S4.1: Add 0.6-0.8wt% lubricant and 1.5-2wt% binder to the powder after insulation coating, mix evenly with a sieve to obtain magnetic powder to be formed; S4.2: Pressing the magnetic powder to be formed into a powder core blank at a pressing pressure of 1800-2000 MPa, and keeping the pressed powder core blank at 700-800° C. for 60-70 min under high vacuum conditions to obtain a semi-finished magnetic powder core; S4.3: Spray insulating coating onto the surface of the semi-finished magnetic powder core, then keep it in an oven at 40-50°C for 1-2h, then keep it at 120-130°C for 2-3h, keep it at 177-180°C for 4-5h, and finally keep it at 200-220°C for 6-7h to obtain the magnetic powder core.

6. The process for preparing a high permeability and low loss magnetic powder core according to claim 4, characterized in that: The ferroboron in step S3.1 is specifically ferroboron with a boron content of 20.3 wt%.

7. The process for preparing a high permeability and low loss magnetic powder core according to claim 4, characterized in that: The ferroniobium in step S3.1 is specifically ferroniobium with a niobium content of 61.2 wt%.

8. The process for preparing a high permeability and low loss magnetic powder core according to claim 4, characterized in that: The ferrophosphorus in step S3.1 is specifically ferrophosphorus with a phosphorus content of 18.5 wt%.

9. The process for preparing a high permeability and low loss magnetic powder core according to claim 5, characterized in that: The lubricant in step S4.1 is zinc stearate lubricant.

10. The process for preparing a high permeability and low loss magnetic powder core according to claim 5, characterized in that: In step S4.1, the adhesive is a silicone resin adhesive.

Citation Information

Cited By

  • High-permeability low-loss nanocrystalline magnetic powder core based on high-resistivity ultrathin insulating layer and preparation method of high-permeability low-loss nanocrystalline magnetic powder core

    CN120376320A